2007
DOI: 10.1513/pats.200607-144jg
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Environment Interactions in Asthma: With Apologies to William of Ockham

Abstract: Many environmental factors and a large number of genetic polymorphisms have been reported to be associated with asthma risk in different locales and at different ages. It seems that what we call asthma is a heterogeneous set of conditions for which the only common feature is recurrent airway obstruction that is at least partially responsive to usual asthma therapy. Recent studies in which environmental factors and genetic variants were studied concomitantly have suggested a potential unifying concept for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…24 In recent years, the suggestion was made that the genetic effects of TLR4 polymorphisms on the biological responses to endotoxin exposure should be considered as controlling factors for work-related respiratory diseases under the concept of a gene-environment interaction. 25 Several studies have been performed to investigate the effects of TLR4 gene polymorphisms on occupational asthma induced by organic dust in, for example, swine farms or laboratories. 26,27 In this study, we found that workers exhibiting variants of the TLR4 promoter at -2027 AϾG and -1608 TϾC had lower work-related lower respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…24 In recent years, the suggestion was made that the genetic effects of TLR4 polymorphisms on the biological responses to endotoxin exposure should be considered as controlling factors for work-related respiratory diseases under the concept of a gene-environment interaction. 25 Several studies have been performed to investigate the effects of TLR4 gene polymorphisms on occupational asthma induced by organic dust in, for example, swine farms or laboratories. 26,27 In this study, we found that workers exhibiting variants of the TLR4 promoter at -2027 AϾG and -1608 TϾC had lower work-related lower respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This theory postulates that reduced exposure to infectious disease and environmental microbial contamination shifts the balance in children's developing immune systems away from fighting infection and toward atopic responses. [32][33][34] Numerous epidemiological associations with asthma and lung development have been documented, including increased body mass, 35,36 exposures to environmental risks (eg, close proximity to major roadways 37,38 ), and use of medications such as antibiotics and antiinflammatory agents. 39,40 There are inconsistencies across studies, and the relative contributions of these and other factors to the increase in asthma prevalence and/or the recent stabilization remain unknown.…”
Section: Asthma Is a Significant Public Health Burden About Which Manmentioning
confidence: 99%
“…There is growing agreement that asthma represents a spectrum of syndromes with multiple complex causes. 12,33,34 Research efforts continue to develop a better understanding of interactions between environmental factors and genotypes/phenotypes and differing susceptibility to risk factors.…”
Section: Asthma Is a Significant Public Health Burden About Which Manmentioning
confidence: 99%
“…There are several possible explanations for these discordant findings including insufficient power, linkage disequilibrium, population admixture, gene/environment (G/E) and gene/gene (G/G) interactions. 6,20 However, more importantly, the lack of replication may be a result of the complex pathogenesis of asthma, which involves genetic heterogeneity and polygenic mode of inheritance, with numerous disease-causing alleles of likely incomplete penetrance, individually small effects, possible parent of origin imprinting and co-existent environmental risk factors.…”
Section: Asthma Geneticsmentioning
confidence: 99%
“…This is not unexpected considering allelic heterogeneity 17 and gene-by-environment interactions. 20 …”
Section: Findings In Several Gwa Studies On Asthmamentioning
confidence: 99%